Analisis Kebutuhan Biaya Renovasi Rumah Layak Huni Kelurahan Sail Kecamatan Tenayan Raya - Sapriani, Yunita; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
A house is a building that functions as a place of residence or residence and a means of fostering a family. Each region has the same problem in terms of settlements, namely the number of habitable houses available is not in accordance with the rate of population growth. Likewise in the city of Pekanbaru, especially in the District of Sail District Tenayan Raya which is the center of government. The study was entitled Estimating the Need for Renovation of Livable Houses in Sail Sub-District, Tenayan Raya, aimed at analyzing uninhabitable homes in the Sail District of Tenayan Raya according to the questionnaire to be distributed to the community and calculating the estimated cost of renovation needed for the construction of unfit houses habitation becomes habitable. The population in this study were people in the Sail District of Tenayan Raya Subdistrict which were as many as 45,307 people with a population of poor 538 people. Determination of the number of samples using Slovin formula and obtained a minimum sample size of 85 people but rounded up to 100 respondents. Data analysis using quantitative descriptive method. The house is said to be uninhabitable is a house with damage of ≥50%. Of the 100 questionnaires distributed and after being processed using the SPSS Statistics 17.0 program, it was found that 14 housing units were severely damaged and categorized as uninhabitable, as many as 86 housing units were categorized as habitable. The houses damaged by walls amounted to 15 houses, roof damage amounted to 21 houses, damaged floors amounted to 2 housing units, and damage to public toilets amounted to 17 housing units. After calculating the budget plan, the cost of Rp. 112,172,160, renovation of roof damage of Rp. 18,268,215, renovation of floor damage of Rp. 1,346,276, and renovation of MCK damage amounting to Rp. 18,127,100. So as to make the house livable, a fee of Rp. 149,914,231. Keywords: Estimates, Needs, Renovation Costs, Livable Houses